Off the record [large type] - Davis, Susan Page (Davis, Susan Page. Mainely romance ;, 2023)
"Wynne's just doing her job, but Andrew doesn't see it that way. Wynne Harding's new job as a reporter challenges her to the limit. She loves writing and telling people's stories, but some articles are difficult to handle. She inadvertently offends farmer Andrew Cook when covering the story of his daughter's injury. Andrew's grandparents and his four-year-old twins love Wynne and hope to draw her into their family circle, but Andrew makes her uncomfortable whenever she's near him. He has no use for reporters and dislikes the way they tend to sensationalize their reporting. Although Wynne's articles seem to have a balanced, sensitive touch, he doesn't dare to let his guard down around her. Can he overcome his distrust of journalists to pursue a friendship with Wynne?"--